STRATEGI PENANGANAN KREDIT BERMASALAH PADA KOPERASI SIMPAN PINJAM PEMBIAYAAN SYARIAH MITRA MASYARAKAT KOTA PONTIANAK - Eka Wulandari; F.Y. Khosmas; Husni Syahrudin (Universitas Tanjungpura, 2022)
Abstrack This study aims to find out how the strategy for bad credit problems and the form of strategy for implementing bad loans in sharia financing savings and loan cooperatives, Pontianak City Independent Partners for the 2015-2019 financial year. The research method used in this research is qualitative research with descriptive method. The sources of data in this study were the chairman of the cooperative, and several administrative staff at the sharia financing savings and loan cooperative, the independent partner of Pontianak City. Data collection techniques in this study are through observation, documentation and interviews. The results of the study show that there are several factors for the occurrence of bad loans in the Islamic savings and loan cooperatives, the independent partners of the city of Pontianak. These factors are internal and external factors. However, the cooperative has several strategies that are implemented to minimize and reduce the number of bad loans in sharia financing savings and loan cooperatives as community partners in the city of Pontianak. With the implementation of these strategies, it is expected to reduce the number of bad loans experienced by the community partner Islamic savings and loan cooperatives. Keywords: Bad Credit, Sharia Cooperatives, Strategy.